Maritime Policy Design Framework with ESG Performance Approach: Case of Estonia - Kaidi Nõmmela; Kati Kõrbe Kaare (Economies, 2022)
In policy-making, the design of a policy is considered to be one of the most significant steps. A well designed policy will be able to solve sectoral problems across stakeholders as well as support the competitive development of the entire economy. Enterprises of the maritime sector have been influenced by environmental, social, and governance (ESG) changes with the push coming from financiers, insurers, regulators, and customers. To meet the ESG challenges and utilize the benefits ahead, they need to be addressed in the new policy design processes. The specificities of a maritime sector as well as science-based policy-making framework are the fundamentals of successful maritime policy development. Estonia is located on the eastern border of the EU, and has always aimed to be a maritime state. National maritime policy has been adopted (2012–2020) and currently, the Estonian Transport and Mobility Master Plan incorporates maritime aspects. Actors of the maritime sector have remained dissatisfied and advocate the reinstatement and redevelopment of Estonian maritime policy. The aim of this study was to present a framework for the design of maritime policy that uses maritime economics, ESG performance goals, and policy design analyses as inputs. As a result, a maritime policy design framework is proposed.